Strategi Peningkatan Kinerja SDM Perangkat Desa Melalui Analisis Swot di Pemerintahan Desa Pangkalan Lunang - Zulfan Amirul Ghozali; Yeni Oktaviani (Pajak dan Manajemen Keuangan, 2025)
This Development Project aims to analyze and formulate strategies for improving the performance of Human Resources (HR) among village officials in the Pangkalan Lunang Village Government by applying the SWOT analysis approach. The performance of village officials plays a crucial role in implementing various village development programs, as they serve as the front line in carrying out government policies. This project employs a qualitative method with data collection techniques including in-depth interviews, observations, and document studies. The SWOT analysis results indicate that village officials in Pangkalan Lunang Village possess several strengths, such as high dedication and a strong understanding of their duties and responsibilities. However, they also face weaknesses such as limited training opportunities and low managerial capacity. The analysis further reveals several opportunities that can be leveraged, including government policy support and available training programs, as well as challenges like low community participation in village development activities. Based on these findings, this Development Project proposes strategies to enhance the performance of village officials, including capacity building through regular training, increasing community participation, and strengthening coordination among related institutions. It is expected that the proposed strategies will improve the efficiency and effectiveness of village officials’ performance in supporting development in Pangkalan Lunang Village.